An in vitro assessment of ionizing radiation impact on the efficacy of radiotherapy for breast cancer - Girgin Merve; Akat Ayberk; Akgül Büşra; Nalbant Nilgül; Karaçetin Didem; Abamor Emrah Şefik; Uğurel Osman Mutluhan; Turgut-Balik Dilek (Türk Biyokimya Dergisi)
Ionizing radiation is still one of the most effective treatment options for various cancers. It is possible to reduce the side effects of this effective treatment method and increase the chance of success by elucidating the responses it creates at the molecular level in the cell. This study aims to investigate of the molecular effects of therapeutic ionizing radiation on breast cancer, which is the most prevalent cancer type.